Are genetic variants for tobacco smoking associated with cannabis involvement?. (1st May 2015) - Agrawal, Arpana; Lynskey, Michael T.; Kapoor, Manav; Bucholz, Kathleen K.; Edenberg, Howard J.; Schuckit, Marc; Brooks, Andrew; Hesselbrock, Victor; Kramer, John; Saccone, Nancy; Tischfield, Jay; Bierut, Laura J.
Highlights: Rs6265 in BDNF is associated with smoking initiation and cannabis use. rs1451240 in CHRNB3 is associated with cannabis dependence. Associations between nicotine-related SNPs and cannabis involvement are not independent of tobacco smoking. Abstract: Background: Cannabis users are highly likely to also be tobacco cigarette smokers and a proportion of this comorbidity is attributable to shared genetic influences. Three large meta-analyses of genomewide association studies (GWAS) of tobacco smoking have identified multiple genomewide significant ( p  < 5 × 10 −8 ) single nucleotide polymorphisms (SNPs). We examine whether these SNPs are associated with tobacco smoking and with cannabis involvement in an independent sample. Method: Eleven SNPs associated with cigarettes per day (CPD), ever versus never smoking and current smoking/smoking cessation at p  < 5 × 10 −8 were selected from three published meta-analyses. Association analyses were conducted with similar tobacco smoking measures in 2716 European-American subjects from the Study of Addictions Genes and Environment (SAGE) and with lifetime and current cannabis use and DSM-IV cannabis abuse/dependence. Results: Cannabis use and tobacco smoking correlated at 0.54. Rs16969968 in CHRNA5 (and its proxy, rs1051730 in CHRNA3) and rs1451240, a proxy for rs13280604 in CHRNB3, were associated with CPD after Bonferroni correction ( p  < 0.006). rs1451240 was also associated with DSM-IV cannabis abuse/dependence. Rs6265 in BDNF was associated with smoking initiation, as in the original meta-analysis and also with lifetime cannabis use. Associations with cannabis involvement were no longer significant upon adjustment for the tobacco smoking measures. Conclusions: The modest associations between cannabis involvement and SNPs for tobacco smoking were not independent of the comorbidity between tobacco and cannabis involvement. Larger samples of individuals might be required to articulate the specific genetic architecture of cannabis involvement.